Factors associated with never‐use of long‐acting reversible contraception among adult reproductive‐aged women in Ohio. Issue 1 (6th November 2022) - Chakraborty, Payal; Chettri, Shibani; Gallo, Maria F.; Smith, Mikaela H.; Hood, Robert B.; Bessett, Danielle; Casterline, John B.; Norris, Alison H.; Turner, Abigail Norris
Abstract: Background: The number of women using long‐acting reversible contraception (LARC)—intrauterine devices (IUDs) and implants—is increasing and 14% of contraceptive users in the United States adopt LARC. We examined correlates of LARC never‐use in a population‐based survey of reproductive‐aged women in Ohio. Methods: We analyzed data from the 2018‐19 Ohio Survey of Women . We examined the prevalence of LARC never‐use and reasons for never‐use among ever users of contraception ( N  = 2388). Using Poisson regression to generate prevalence ratios (PRs), we examined associations between selected correlates (demographic factors, healthcare access/quality measures, and religious/political views) and LARC never‐use. Results: Most Ohio women (74%) had never used LARC. Commonly reported reasons for not using an IUD or an implant were preferring a different method (46% and 45%, respectively), not wanting an object inside their body (45% and 43%), side effect concerns (39% and 33%), insertion/removal concerns (31% and 25%), and unfamiliarity (13% and 20%). Conservative political views (PR: 1.12, 95% confidence interval [CI]: 1.04–1.22), pro‐life affiliation (PR: 1.11, 95% CI: 1.02–1.20), placing high importance on religion in daily life (PR: 1.15, 95% CI: 1.06–1.26), and being non‐Hispanic white as compared to non‐Hispanic Black (PR: 1.20, 95% CI: 1.02–1.41) were significantly associated with LARC never‐use. Findings were generally similar for models analyzing IUD and implant never‐use separately. Conclusions: Among ever‐users of contraception, LARC never‐use was associated with having conservative political views, being religious, and having a pro‐life affiliation. Except for race/ethnicity, demographic and healthcare measures were not associated with LARC never‐use among women in Ohio.